Electroless Deposition of Pure Co on TaN Substrate for Interconnect Metallization. Issue 7 (1st July 2022) - Qiu, Li-Na; Ni, Zi-Hong; Wang, Ying-Jie; Hu, Chun-Feng; Qu, Xin-Ping
Abstract : This work explores the electroless deposition of pure Co film on TaN substrate using Ti 3+ as a reducing agent for interconnect metallization. Continuous and dense electroless-deposited (ELD) Co thin films with low surface roughness are obtained on the blanket and patterned structures using colloidal Sn/Pd activation. The effects of the Pd activation process on the Co nucleation, growth mechanisms, and the properties of the deposited Co films have been investigated in detail. The properties of the activated Pd nuclei decide the morphology and quality of the ELD Co films. The XPS results indicate that the ELD Co film is nearly pure Co film, with the metallic Co concentration of 99.2 at% and 99.4 at% for the as-deposited and annealed films, respectively. The resistivity of the Co film in 60 nm thick is as low as 13.6 μ Ω·cm. Our results reveal that the ELD Co film is nanocrystalline with a mixture of the HCP and FCC structures. Further, the conformal ELD Co layer with good step coverage is deposited into the nanoscale trenches.